Physical match profiles for establishing positionspecific training and rehabilitation protocols for beach volleyball players - Medeiros, A. I. A.; Lopez-Martinez, A.-B.; Palao, J.-M. (Medicine & Science in Sports & Exercise, 2014)
Strength and physical training and the final phase of rehabilitation protocols must take into consideration the sport´s demands and the player´s playing position to be specific. PURPOSE: The purpose of this study was to establish the frequency and type of actions executed in beach volleyball according to players´ sex and playing function (i.e. blocker, defender or universal). METHODS: The sample consisted of 69 sets (2708 rallies) of the 2008 Olympic Games, played by 48 female beach volleyball players, and 40 sets (1480 rallies) of the 2011 World Championships, played by 106 male beach volleyball players. Only the two first sets of the matches were utilized in this study (21-point sets). The physical actions studied included static jumps (blocks), dynamic jumps (with an approach run; i.e. jump serves and spikes), and hits (serves and spikes). The matches were analyzed through systematic observation by two experienced and trained observers (interobserver reliability index of 0.93 and intra-observer reliability index of 0.98). The unit of analysis was the set. Descriptive statistics and the Wilcoxon test were used to determine differences between players of different playing functions. RESULTS: Significant differences were found in the physical actions executed by players between all playing positions for both women´s and men´s beach volleyball players (p<.001). CONCLUSION: Players of different playing positions require training with different types and amounts of actions in order to be properly prepared for the game demands. The reference values provided can be used to establish the game demands and guide the design of training workouts and the last phase of rehabilitation protocols.